Different exosomes are loaded in hydrogels for the application in the field of tissue repair - Zhang, Yanyan; Yan, Wenjing; Wu, Le; Yu, Zihao; Quan, Ying; Xie, Xin (Frontiers in Bioengineering and Biotechnology, 2025)
Exosomes are double-membrane vesicular nanoparticles in the category of extracellular vesicles, ranging in size from 30 to 150 nm, and are released from cells through a specific multi-step exocytosis process. Exosomes have emerged as promising tools for tissue repair due to their ability to transfer bioactive molecules that promote cell proliferation, differentiation, and tissue regeneration. However, the therapeutic application of exosomes is hindered by their rapid clearance from the body and limited retention at the injury site. To overcome these challenges, hydrogels, known for their high biocompatibility and porous structure, have been explored as carriers for exosomes. Hydrogels can provide a controlled release mechanism, prolonging the retention time of exosomes at targeted tissues, thus enhancing their therapeutic efficacy. This review focuses on the combination of different exosomes with hydrogels in the context of tissue repair. We first introduce the sources and functions of exosomes, particularly those from mesenchymal stem cells, and their roles in regenerative medicine. We then examine various types of hydrogels, highlighting their ability to load and release exosomes. Several strategies for encapsulating exosomes in hydrogels are discussed, including the impact of hydrogel composition and structure on exosome delivery efficiency. Finally, we review the applications of exosomes-loaded hydrogels in the repair of different tissues, such as skin, bone, cartilage, and nerve, and explore the challenges and future directions in this field. The combination of exosomes with hydrogels offers significant promise for advancing tissue repair strategies and regenerative therapies.